2015
DOI: 10.17109/azh.61.4.341.2015
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of Sesamia nonagrioides (Lepidoptera: Noctuidae) in Iran inferred from mitochondrial DNA

Abstract: Although the stem borer Sesamia nonagrioides (Lefèbvre, 1827) is one of the most destructive agricultural pests in South and Southwest Iran, the structure of these populations is not yet well understood. In this study, we sequenced two mitochondrial genes (CO1 and Cyt-b) of populations collected in cultivated sugarcane and rice in South and Southwest Iran. These genetic data of Iranian populations were compared with those of already published data from West Palaearctic (Africa and Europe). To testing the intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Of the remaining species, some, although widespread, damage rice in relatively localized regions: For example, S. nonagrioides that occurs around the Adriatic Sea and Persian Gulf, although it attacks rice in southern Europe, is more commonly associated with maize [40,52,193]. The species has also been reported from sugarcane in Iran apparently without attacking adjacent rice fields [194,195]. In West Africa, the subspecies Sesamia nonagrioides botanephaga Tams and Bowden is also more prevalent in maize and sugarcane [32,101,166].…”
Section: Africa and The Mediterraneanmentioning
confidence: 99%
“…Of the remaining species, some, although widespread, damage rice in relatively localized regions: For example, S. nonagrioides that occurs around the Adriatic Sea and Persian Gulf, although it attacks rice in southern Europe, is more commonly associated with maize [40,52,193]. The species has also been reported from sugarcane in Iran apparently without attacking adjacent rice fields [194,195]. In West Africa, the subspecies Sesamia nonagrioides botanephaga Tams and Bowden is also more prevalent in maize and sugarcane [32,101,166].…”
Section: Africa and The Mediterraneanmentioning
confidence: 99%
“…Many authors [55,56] have considered S. nonagrioides as a sedentary species. In our study, significant genetic structure was observed among sampling sites (F ST = 0.04, 17% of variance explained in PAMOVA).…”
Section: Existence and Nature Of Genetic Structure Depend On The Hostmentioning
confidence: 99%
“…Sampling of the MCB in uncultivated areas must therefore be carried out all across Europe, especially because the biotope favorable to its development, i.e. river banks, ponds, wetlands, estuaries as occurring in the Rhone Valley, in Africa [59] or in Iran [56,60] exists all over Europe.…”
Section: Implication For Mcb Managementmentioning
confidence: 99%
“…Nevertheless, despite its high level of specialization in maize, S. nonagrioides has shown a certain degree of polyphagy, since it has been recorded in a wide range of cultivated and wild host species of the Poaceae, Cyperaceae and Thyphaceae families across its distribution range 25,26 . Regarding cultivated plants, S. nonagrioides is known to be a major pest of sorghum 27,28 and rice 29,30 . The degree of polyphagy has usually been considered an important factor for resistance development, although some studies have not found a clear causal relationship between both evolutionary phenomena 31 .…”
Section: Introductionmentioning
confidence: 99%